The British party funding regime at a critical juncture? Applying new institutional analysis. (May 2017) - Power, Sam
This article analyses the state of play regarding party funding reform in British Politics through the application of new institutionalism. It then investigates whether the Collins Review of 2014 represents a critical juncture in the evolution of the political finance regime. Utilising elite interview and documentary research, the article argues that the removal of a key institutional stumbling block – the concession of the opt-in for trade union members of the Labour party – has created a situation which may have a very real effect on both British party funding and how we understand party finance reform more generally.